Memajukan Pustakawan Sekolah Melalui Penguatan Literasi Informasi Advanced Information Retrieval dengan Teknologi Gscholar untuk Temu Kembali Informasi yang Unggul - Windah, Andi; Putra, Purwanto; Arnila, Purnamayanti; Eri, Maryani (FT Universitas Lampung, 2023)
The fact that school librarians possess expertise in an array of search engines suitable for meeting the information requirements of students, they frequently encounter impediments in utilizing such resources, including administrators and ATPUSI constituents in the Lampung Province. The community service activities, offered as Gscholar Advanced Search Operators Technology Training for Information Retrieval, have been implemented to enhance the information literacy skills of administrator librarians and members of the Association of Technical and Professional Staff of Universities and Institutions (ATPUSI) in Lampung Province. The ultimate objective of these activities is to facilitate the utilization of GScholar technology in an efficient and effective manner. By joining Focus Group Discussions (FGD) and offering instructional resources concerning the utilization of Google Scholar technology, school librarians can enhance the precision of information, as well as aid them in fostering the development of information literacy competencies among students and educators. In addition, this approach can bolster their collaborative aptitude for attaining impactful and dependable information. The execution of the activity shall transpire in July of 2023, employing pedagogical approaches involving lecturing, question-response exchanges, and evaluation techniques. The assessment shall be conducted by means of pre-designed questionnaires. In this community service activity, inquiries incorporating pre-test and post-test measures are employed to ascertain the level of comprehension attained. The outcomes of this service demonstrate an augmentation in the discernment and proficiency of academic librarians concerning the utilization of Gscholar Advanced Search Operators for information retrieval. Furthermore, the results indicate an amplified recognition and comprehension regarding the significance of precise information in effectively promoting the enhancement of information literacy skills among the service beneficiaries.